Pre‐ and post‐serial metagenomic analysis of gut microbiota as a prognostic factor in patients undergoing haematopoietic stem cell transplantation. (30th September 2019) - Kusakabe, Shinsuke; Fukushima, Kentaro; Maeda, Tetsuo; Motooka, Daisuke; Nakamura, Shota; Fujita, Jiro; Yokota, Takafumi; Shibayama, Hirohiko; Oritani, Kenji; Kanakura, Yuzuru
Summary: The human gut harbours diverse microorganisms, and gut dysbiosis has recently attracted attention because of its possible involvement in various diseases. In particular, the lack of diversity in the gut microbiota has been associated with complications of haematopoietic stem cell transplantation (HSCT), such as infections, acute graft‐versus‐host disease and relapse of primary disease, which lead to a poor prognosis. However, few studies have serially examined the composition of the intestinal microbiota after HSCT. In this study, we demonstrated, using next‐generation sequencing of the bacterial 16S ribosomal RNA gene, combined with uniFrac distance analysis, that the intestinal microbiota of patients undergoing allogeneic HSCT substantially differed from that of healthy controls and recipients of autologous transplants. Faecal samples were obtained daily throughout the clinical course, before and after transplantation. Notably, the proportions of Bifidobacterium and genera categorized as butyrate‐producing bacteria were significantly lower in patients with allogeneic HSCT than in healthy controls. Furthermore, among allogeneic transplant recipients, a subgroup with a preserved microbiota composition showed a benign course, whereas patients with a skewed microbiota showed a high frequency of complications and mortality after transplantation. Thus, we conclude that the stability of intestinal microbiota is critically involved in outcomes of HSCT.